Aligning responsible business practices: A case study. (6th July 2017) - Weller, Angeli E.
Abstract: This article offers an in‐depth case study of a global high tech manufacturer that aligned its ethics and compliance, corporate social responsibility, and sustainability practices. Few large companies organize their responsible business practices this way, despite conceptual relevance and calls to manage them comprehensively. A communities of practice theoretical lens suggests that intentional effort would be needed to bridge meaning between the relevant managers and practices in order to achieve alignment. The findings call attention to the important role played by employees who broker understanding between managers and practices, and the boundary objects used to create shared meaning and engagement. They also highlight that an organizing logic is necessary but not sufficient to align practices. This study describes the dynamics of alignment and provides a practical road map for scholars and managers interested in understanding how responsible business practices may be collectively organized.